Heat-reflective heat-insulating powder coating and preparation method thereof

By modifying the coupling agent of hollow glass microbeads and glass powder, the compatibility with polyester resin is improved, and a stable cross-linking network is formed, which solves the problem of poor compatibility between inorganic fillers and resins, and significantly improves the weather resistance and thermal insulation properties of the coating.

CN118931333BActive Publication Date: 2025-04-18FOSHAN JUNMEIQI NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411184485.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-04-18
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The compatibility between inorganic pigment fillers and resins in existing powder coatings is poor, resulting in uneven dispersion of fillers in the matrix, affecting the performance of the coating.

Method used

The hollow glass microbeads are modified by composite coupling agent, and the glass powder is modified by organic chromium compound coupling agent to increase its compatibility with polyester resin and form a stable three-dimensional crosslinking network.

Benefits of technology

The weather resistance and mechanical strength of the coating are improved, the thermal insulation and thermal reflection properties are enhanced, and the interface bonding between the filler and the resin is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005013138190000081
    Figure BDA0005013138190000081
Patent Text Reader

Abstract

The present application relates to the field of powder coatings, and specifically discloses a heat-reflecting heat-insulating powder coating and a preparation method thereof. The raw materials for preparing the heat-reflecting heat-insulating powder coating include polyester resin, hollow glass microspheres modified by a composite coupling agent, glass powder modified by an organic chromium compound, a curing agent, glass fiber powder, a leveling agent, and a degassing agent. The present application modifies the hollow glass microspheres by a composite coupling agent, and modifies the glass powder by an organic chromium compound coupling agent. One end of the coupling agent molecule is connected to the hollow glass microspheres or glass powder through a chemical reaction, and the other end is cured and cross-linked with the active group of the resin, thereby increasing the compatibility of the hollow glass microspheres and glass powder with the matrix resin, so that the powder coating has excellent heat-insulating properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of powder coatings, and in particular to a heat-reflecting heat-insulating powder coating and a preparation method thereof. Background Art

[0002] Powder coating is a kind of coating containing pure solids, which is applied and coated in powder form. Powder coating is different from general solvent-based coating and water-based coating in that it does not use organic solvent or water as dispersion medium, but uses air as dispersion medium. It is stable in storage at room temperature, and after electrostatic spraying or fluidized bed dipping, it is melted and solidified by heating and baking to form a smooth permanent coating film, thus achieving the purpose of decoration and weather resistance.

[0003] Powder coatings are generally prepared by mixing resins, curing agents, pigments and other additives in a certain proportion, extruding, crushing, screening and other processes. For example, when hollow glass microspheres are used as fillers, the characteristics of hollow spheres containing a certain amount of gas inside make powder coatings have excellent thermal insulation properties. However, due to the large particle size of individual hollow glass microspheres, their surface area is also correspondingly increased, and interfacial stress problems may occur during contact with film-forming resins, resulting in poor compatibility between hollow glass microspheres and matrix resins. At the same time, other inorganic fillers may also have weak interfacial bonding with the matrix resin, resulting in uneven dispersion of fillers in the matrix, prone to agglomeration and other phenomena, which affects the performance of the coating. Summary of the invention

[0004] In order to improve the compatibility between inorganic pigments and fillers and resins, the present application provides a heat-reflective heat-insulating powder coating and a preparation method thereof.

[0005] In the first aspect, the present application provides a heat-reflective heat-insulating powder coating, which adopts the following technical solution:

[0006] A heat-reflective heat-insulating powder coating is prepared from the following raw materials in parts by weight:

[0007] 60-70 parts of polyester resin, 10-14 parts of composite coupling agent modified hollow glass microspheres, 9-13 parts of organic chromium compound modified glass powder, 3-5 parts of curing agent, 1-2 parts of glass fiber powder, 1.5-1.9 parts of leveling agent, and 1.2-1.6 parts of degassing agent.

[0008] By adopting the above technical scheme, the powder coating uses polyester resin as the base resin, the hollow glass microspheres are modified by a composite coupling agent, and the glass powder is modified by an organic chromium compound coupling agent. One end of the coupling agent molecule is connected to the hollow glass microspheres or glass powder through a chemical reaction, and the other end is cured and cross-linked with the active group of the resin, thereby increasing the compatibility of the hollow glass microspheres and glass powder with the base resin, and forming a stable three-dimensional cross-linked network with a suitable cross-linking density, thereby improving the weather resistance of the coating and slowing down the aging of the coating. Among them, the lower interfacial free energy of the coupling agent molecules is conducive to uniform dispersion in the resin matrix, and the composite coupling agent plays an important role in improving the interface bonding between the hollow glass microspheres and the resin matrix. In addition, the hollow glass microspheres have excellent heat insulation properties due to their hollow and spherical properties that contain a certain amount of gas, and the surfaces of the hollow glass microspheres and glass powder can reflect the visible light and near-infrared light in the sunlight multiple times, so that the coating with the addition of glass microspheres has very good heat reflection properties. Adding glass fiber powder can compensate for the decrease in coating strength caused by the addition of microbeads and effectively improve the mechanical strength of the coating.

[0009] Preferably, the composite coupling agent modified hollow glass microspheres are prepared from a silane coupling agent, an aluminate coupling agent and hollow glass microspheres, and the weight ratio of the silane coupling agent, the aluminate coupling agent and the hollow glass microspheres is (0.6-0.8):(0.2-0.4):10; the organic chromium compound modified glass powder is prepared from a methacryloyl chromium complex and glass powder, and the weight ratio of the methacryloyl chromium complex and the glass powder is (0.3-0.5):12.

[0010] Preferably, the silane coupling agent is at least one of (3-mercaptopropyl)methyldimethoxysilane and (3-mercaptopropyl)triethoxysilane; the aluminate coupling agent is at least one of di(distearic acid glyceryl)aluminate isopropyl and di(tristearic acid pentaerythritol)aluminate isopropyl.

[0011] By adopting the above technical solution, the silane coupling agent is hydrolyzed to produce hydroxyl groups, which are combined with the hydroxyl groups on the surface of the hollow glass microspheres, and dehydration condensation generates hydrogen bonds, which are beneficial to improving the wettability of the hollow glass microspheres. At the same time, the thiol groups in the silane coupling agent undergo a cross-linking reaction with the carboxyl groups in the resin. The silane coupling agent molecules act as a "bridge" between the resin and the hollow glass microspheres, generating a strong force, thereby promoting and improving the interfacial bonding between the resin and the microspheres. The alkoxy groups in the aluminate coupling agent are hydrolyzed and combined with the hydroxyl groups on the surface of the hollow glass microspheres to form an organic active monolayer on the surface of the microspheres, further improving the interfacial bonding between the resin and the microspheres. Both the silane coupling agent and the aluminate coupling agent have a synergistic effect on the hollow glass microspheres, and the compatibility between the modified hollow glass microspheres and the matrix resin is optimal. The molecular structure of the methacryloyl chromium complex contains unsaturated double bonds and Cr 3+ The unsaturated double bond at one end reacts with the resin molecule, and the other end combines with the silicon-oxygen bond on the surface of the glass powder particle through its own chromium-oxygen bond to form a new chemical bond, thereby improving the compatibility of the glass powder and the matrix resin.

[0012] Preferably, the polyester resin is a carboxyl-terminated polyester resin, and the acid value of the carboxyl-terminated polyester resin is 40-60 mgKOH / g and the molecular weight is 4000-6000.

[0013] By adopting the above technical scheme, the appropriate acid value provides certain carboxyl reaction sites for the polyester resin, increases the chemical reaction ability with other materials, and helps to improve the crosslinking density and mechanical strength of the material. At the same time, the appropriate molecular weight increases the entanglement degree of the molecular chain of the resin molecule, which improves the mechanical strength of the material without affecting the fluidity and processing performance of the resin.

[0014] Preferably, the particle size of the hollow glass microspheres is 20-40 μm, and the particle size of the glass powder is 4-8 μm.

[0015] By adopting the above technical solution, the hollow glass microspheres with moderate particle size have a lower density, which can significantly reduce the overall weight of the material without sacrificing the structural strength of the material. Glass powder has a smaller particle size and good dispersibility. In powder coatings, glass powder can increase the fullness of the coating, and at the same time has a matting effect, improving the weather resistance of the paint film.

[0016] Preferably, the curing agent is at least one of N,N,N',N'-tetrakis(β-hydroxyethyl)-1,4-cyclohexanediamide and N,N'-bis(β-hydroxyethyl)adipamide.

[0017] By adopting the above technical solution, the hydroxyl group in the curing agent and the carboxyl group in the polyester undergo esterification reaction to crosslink and form a film. Among them, the activation energy of hydroxyalkylamide is low and it can be cured at low temperature, and only water molecules are released in the esterification reaction, which will not cause pollution to the environment.

[0018] Preferably, the leveling agent is at least one of polyacrylate and silicon-containing acrylate.

[0019] By adopting the above technical solution, when the acrylic polymer is added to the reaction system, the leveling agent will migrate to the surface of the molten resin. This migration is generally strengthened due to its incompatibility with the coating system. When the acrylic polymer reaches the surface, its polar main chain remains in the molten resin, while the alkyl side chain tends to escape to the outside and reach a stable equilibrium state. Therefore, due to the relatively high concentration of the molecular structure arranged in a directional manner on the entire surface, the entire surface tension tends to be average, thereby eliminating the original surface tension inhomogeneity and reducing the unevenness of the coating surface.

[0020] Preferably, the degassing agent is at least one of ethylene bisstearamide and hydrogenated castor oil.

[0021] By adopting the above technical solution, the degassing agent can further control the generation and elimination of bubbles by reducing the viscosity and surface tension of the melt, so that the coating film can continue to unfold, and there is enough time for the air to escape from the coating film. It can effectively eliminate the pinholes, shrinkage holes and bubbles generated by the powder coating during the curing process, thereby improving the quality and smoothness of the coating.

[0022] In a second aspect, the present application provides a method for preparing a heat-reflective heat-insulating powder coating, which adopts the following technical solution:

[0023] A method for preparing a heat-reflective heat-insulating powder coating comprises the following steps:

[0024] The raw materials are weighed according to the component ratio, the polyester resin is heated to 150-170°C, and then hollow glass microspheres modified by composite coupling agent, glass powder modified by organic chromium compound, curing agent, glass fiber powder, leveling agent and degassing agent are added and mixed at high speed for 20-30 minutes, the uniformly mixed materials are mixed and extruded, and after discharging, the sheets are pressed and cooled to room temperature, and then sieved after high-speed crushing to obtain heat-reflective heat-insulating powder coating.

[0025] By adopting the above technical scheme, the hollow glass microspheres are modified by a composite coupling agent and the glass components are modified by an organic chromium compound, which effectively improves the poor compatibility of the hollow glass microspheres and glass powder with the resin, enhances the interfacial bonding force with the resin, and improves the performance of the powder coating.

[0026] Preferably, the preparation method of the composite coupling agent modified hollow glass microspheres is:

[0027] ① Place the hollow glass microspheres in a NaOH solution, stir at 50-60°C for 3-4 hours, then wash with deionized water and alcohol alternately, filter under reduced pressure to remove excess water, and dry to obtain pretreated hollow glass microspheres;

[0028] ② The silane coupling agent and the aluminate coupling agent are mixed to obtain a composite coupling agent, and then the composite coupling agent is added to an ethanol solution, the pH is adjusted to 5.0-7.0, and hydrolyzed for 1-2 hours to obtain a hydrolyzed coupling agent solution, and then the pretreated hollow glass microspheres are added to the hydrolyzed coupling agent solution, stirred at 50-60°C for 3-4 hours, and then washed alternately with deionized water and alcohol, and dried at 70-80°C for 10-12 hours to obtain composite coupling agent modified hollow glass microspheres.

[0029] By adopting the above technical solution, the hollow glass microspheres are pretreated to increase the content of hydroxyl groups on the microsphere surface, and the excess coupling agent molecules on the microsphere surface can be removed by washing with deionized water and alcohol.

[0030] Preferably, the preparation method of the organic chromium compound modified glass powder is:

[0031] ① Place the glass powder in a NaOH solution, stir at 50-60°C for 3-4 hours, then wash with deionized water and alcohol alternately, filter under reduced pressure to remove excess water, and dry to obtain pretreated glass powder;

[0032] ② Add the pretreated glass powder to the methacryloyl chromium complex, stir at 50-60°C for 3-4 hours, then wash with deionized water and alcohol alternately, and dry at 70-80°C for 10-12 hours to obtain the organic chromium compound modified glass powder.

[0033] By adopting the above technical solution, the glass powder is pretreated to increase the hydroxyl content on the surface, which is beneficial to react with the coupling agent molecules and thus improve the compatibility of the glass powder and the resin.

[0034] This application has the following beneficial effects:

[0035] In the present application, the powder coating uses polyester resin as the matrix resin, the hollow glass microspheres are modified by a composite coupling agent, and the glass powder is modified by an organic chromium compound coupling agent. One end of the coupling agent molecule is connected to the hollow glass microspheres or glass powder by a chemical reaction, and the other end is cured and cross-linked with the active group of the resin, increasing the compatibility of the hollow glass microspheres and the glass powder with the matrix resin, and forming a stable three-dimensional cross-linked network with a suitable cross-linking density, thereby improving the weather resistance of the coating and slowing down the aging of the coating. Among them, the lower interfacial free energy of the coupling agent molecules is conducive to uniform dispersion in the resin matrix, and the composite coupling agent plays an important role in improving the interface bonding between the hollow glass microspheres and the resin matrix. In addition, the hollow glass microspheres have excellent heat insulation properties due to the characteristics of a certain amount of gas wrapped inside the sphere, and the hollow glass microspheres and the glass powder surface can reflect the visible light and near-infrared light in the sunlight multiple times, so that the coating with the addition of glass microspheres has very good heat reflection properties. Adding glass fiber powder can compensate for the decrease in coating strength caused by the addition of microbeads and effectively improve the mechanical strength of the coating. DETAILED DESCRIPTION

[0036] Preparation Example

[0037] Preparation Example 1

[0038] The preparation method of composite coupling agent modified hollow glass microspheres is as follows:

[0039] ① Place 10 kg of hollow glass microspheres (particle size of 20 μm) in a NaOH solution, stir at 50° C. for 3 h, then wash with deionized water and alcohol alternately for 3 times, filter under reduced pressure to remove excess water, and dry to obtain pretreated hollow glass microspheres; ② Mix 0.6 kg of (3-mercaptopropyl) methyldimethoxysilane and 0.2 kg of di(distearic acid glyceryl)aluminate isopropyl to obtain a composite coupling agent, then add the composite coupling agent to an ethanol solution, add a small amount of glacial acetic acid to adjust the pH to 5.0, hydrolyze for 1 h to obtain a hydrolysis coupling agent solution, then add the pretreated hollow glass microspheres to the hydrolysis coupling agent solution, stir at 50° C. for 3 h, then wash with deionized water and alcohol alternately for 3 times, and dry at 70° C. for 10 h to obtain composite coupling agent modified hollow glass microspheres.

[0040] The preparation method of the organic chromium compound modified glass powder is as follows:

[0041] ① Place 12 kg of glass powder in a NaOH solution, stir at 50 ° C for 3 hours, then wash it with deionized water and alcohol alternately for 3 times, filter under reduced pressure to remove excess water, and dry it to obtain pretreated glass powder;

[0042] ② Add the pretreated glass powder to 0.3 kg of methacryloyl chromium complex, stir at 50° C. for 3 h, then wash it with deionized water and alcohol alternately for 3 times, and dry it at 70° C. for 10 h to obtain an organochromium compound-modified glass powder.

[0043] Preparation Example 2

[0044] The preparation method of composite coupling agent modified hollow glass microspheres is as follows:

[0045] ① Place 10 kg of hollow glass microspheres (particle size 30 μm) in a NaOH solution, stir at 55 ° C for 3.5 h, then wash with deionized water and alcohol alternately for 3 times, filter under reduced pressure to remove excess water, and dry to obtain pretreated hollow glass microspheres;

[0046] ② Mix 0.7 kg (3-mercaptopropyl) triethoxysilane and 0.3 kg di(pentaerythritol tristearate) isopropyl aluminate to obtain a composite coupling agent, then add the composite coupling agent to an ethanol solution, add a small amount of glacial acetic acid to adjust the pH to 6.0, hydrolyze for 1 hour to obtain a hydrolyzed coupling agent solution, then add the pretreated hollow glass microspheres to the hydrolyzed coupling agent solution, stir at 55°C for 3.5 hours, then wash with deionized water and alcohol alternately for 3 times, and dry at 75°C for 11 hours to obtain composite coupling agent modified hollow glass microspheres.

[0047] The preparation method of the organic chromium compound modified glass powder is as follows:

[0048] ① Place 12 kg of glass powder in a NaOH solution, stir at 55 °C for 3.5 h, then wash with deionized water and alcohol alternately for 3 times, filter under reduced pressure to remove excess water, and dry to obtain pretreated glass powder;

[0049] ② Add the pretreated glass powder to 0.4 kg of methacryloyl chromium complex, stir at 55°C for 3.5 hours, then wash it with deionized water and alcohol alternately for 3 times, and dry it at 75°C for 11 hours to obtain organic chromium compound modified glass powder.

[0050] Preparation Example 3

[0051] The preparation method of composite coupling agent modified hollow glass microspheres is as follows:

[0052] ① 10 kg of hollow glass microspheres (particle size of 40 μm) were placed in a NaOH solution, stirred at 60° C. for 4 h, then washed alternately with deionized water and alcohol for 3 times, filtered under reduced pressure to remove excess water, and dried to obtain pretreated hollow glass microspheres; ② 0.8 kg of (3-mercaptopropyl) methyldimethoxysilane and 0.4 kg of di(pentaerythritol tristearate)aluminate isopropyl were mixed to obtain a composite coupling agent, then the composite coupling agent was added to an ethanol solution, a small amount of glacial acetic acid was added to adjust the pH to 7.0, and hydrolyzed for 2 h to obtain a hydrolyzed coupling agent solution, and then the pretreated hollow glass microspheres were added to the hydrolyzed coupling agent solution, stirred at 60° C. for 4 h, then washed alternately with deionized water and alcohol for 3 times, and dried at 80° C. for 12 h to obtain composite coupling agent modified hollow glass microspheres.

[0053] The preparation method of the organic chromium compound modified glass powder is as follows:

[0054] ① Place 12 kg of glass powder in a NaOH solution, stir at 60 ° C for 4 hours, then wash it with deionized water and alcohol alternately for 3 times, filter under reduced pressure to remove excess water, and dry it to obtain pretreated glass powder;

[0055] ② Add the pretreated glass powder to 0.5 kg of methacryloyl chromium complex, stir at 60° C. for 4 h, then wash it with deionized water and alcohol alternately for 3 times, and dry it at 80° C. for 12 h to obtain an organochromium compound-modified glass powder.

[0056] Example

[0057] Example 1

[0058] A heat-reflective heat-insulating powder coating comprises 60kg of carboxyl-terminated polyester resin (acid value 40mgKOH / g, molecular weight 4000), 10kg of composite coupling agent-modified hollow glass microspheres (prepared in Preparation Example 1), 9kg of organic chromium compound-modified glass powder (prepared in Preparation Example 1), 3kg of N,N,N',N'-tetrakis(β-hydroxyethyl)-1,4-cyclohexanediamide, 1kg of glass fiber powder, 1.5kg of polyacrylate (Nouryon GB-50L), and 1.2kg of ethylene bisstearamide.

[0059] The method for preparing the heat-reflective heat-insulating powder coating in this embodiment comprises the following steps:

[0060] The raw materials are weighed according to the component ratio, the carboxyl-terminated polyester resin is heated to 150°C, and then hollow glass microspheres modified by a composite coupling agent, glass powder modified by an organic chromium compound, N,N,N',N'-tetrakis(β-hydroxyethyl)-1,4-cyclohexanediamide, glass fiber powder, polyacrylate, and ethylene bisstearamide are added and mixed at high speed for 20 minutes, the uniformly mixed materials are sent to an extruder for mixing and extrusion, and the materials are pressed into sheets after being discharged and cooled to room temperature, and then sieved after high-speed crushing to obtain a heat-reflective heat-insulating powder coating.

[0061] Example 2

[0062] A heat-reflective heat-insulating powder coating comprises 65kg of carboxyl-terminated polyester resin (acid value 50mgKOH / g, molecular weight 5000), 12kg of hollow glass microspheres modified by a composite coupling agent (prepared in Preparation Example 2), 11kg of glass powder modified by an organic chromium compound (prepared in Preparation Example 2), 4kg of N,N'-bis(β-hydroxyethyl)adipamide, 1.5kg of glass fiber powder, 1.7kg of silicon-containing acrylate (Zhanxin EBECRYL 8890), and 1.4kg of hydrogenated castor oil.

[0063] The method for preparing the heat-reflective heat-insulating powder coating in this embodiment comprises the following steps:

[0064] The raw materials are weighed according to the component ratio, the carboxyl-terminated polyester resin is heated to 160°C, and then hollow glass microspheres modified by a composite coupling agent, glass powder modified by an organic chromium compound, N,N'-bis(β-hydroxyethyl)adipamide, glass fiber powder, silicon-containing acrylate, and hydrogenated castor oil are added and mixed at high speed for 25 minutes, and the uniformly mixed materials are sent to an extruder for mixing and extrusion. After the materials are discharged, they are pressed into sheets and cooled to room temperature, and then sieved after high-speed crushing to obtain a heat-reflective heat-insulating powder coating.

[0065] Example 3

[0066] A heat-reflective heat-insulating powder coating comprises 70kg of carboxyl-terminated polyester resin (acid value 60mgKOH / g, molecular weight 6000), 14kg of hollow glass microspheres modified by a composite coupling agent (prepared in Preparation Example 3), 13kg of glass powder modified by an organic chromium compound (prepared in Preparation Example 3), 5kg of N,N'-bis(β-hydroxyethyl)adipamide, 2kg of glass fiber powder, 1.9kg of silicon-containing acrylate (Zhenxin EBECRYL 8890), and 1.6kg of ethylene bisstearamide.

[0067] The method for preparing the heat-reflective heat-insulating powder coating in this embodiment comprises the following steps:

[0068] The raw materials are weighed according to the component ratio, the carboxyl-terminated polyester resin is heated to 170°C, and then hollow glass microspheres modified by a composite coupling agent, glass powder modified by an organic chromium compound, N,N'-bis(β-hydroxyethyl)adipamide, glass fiber powder, silicon-containing acrylate, and ethylene bisstearamide are added and mixed at high speed for 30 minutes, and the evenly mixed materials are sent to an extruder for mixing and extrusion. After the materials are discharged, they are pressed into sheets and cooled to room temperature, and then sieved after high-speed crushing to obtain a heat-reflective heat-insulating powder coating.

[0069] Example 4

[0070] A heat reflective heat insulating powder coating is different from Example 1 in that: the (3-mercaptopropyl)methyldimethoxysilane in the raw material for preparing the composite coupling agent modified hollow glass microspheres is replaced by an equal amount of 3-aminopropyltrimethoxysilane.

[0071] Example 5

[0072] A heat reflective heat insulating powder coating is different from Example 1 in that: (3-mercaptopropyl)methyldimethoxysilane in the raw material for preparing hollow glass microspheres modified by a composite coupling agent is replaced by an equal amount of γ-(2,3-epoxypropyloxy)propyltrimethoxysilane.

[0073] Comparative Example

[0074] Comparative Example 1

[0075] A heat-reflective heat-insulating powder coating is different from Example 1 in that the composite coupling agent-modified hollow glass microspheres are replaced by an equal amount of hollow glass microspheres, and the organic chromium compound-modified glass powder is replaced by an equal amount of glass powder.

[0076] Comparative Example 2

[0077] A heat-reflective heat-insulating powder coating is different from Example 1 in that the composite coupling agent-modified hollow glass microspheres are replaced by an equal amount of silane coupling agent-modified hollow glass microspheres.

[0078] Comparative Example 3

[0079] A heat-reflective heat-insulating powder coating is different from Example 1 in that the composite coupling agent-modified hollow glass microspheres are replaced by an equal amount of aluminate coupling agent-modified hollow glass microspheres.

[0080] Comparative Example 4

[0081] A heat-reflective heat-insulating powder coating, which differs from Example 1 in that the composite coupling agent-modified hollow glass microspheres are replaced by an equal amount of glass fiber powder.

[0082] Comparative Example 5

[0083] A heat-reflective heat-insulating powder coating, which differs from Example 1 in that the organic chromium compound-modified glass powder is replaced by an equal amount of glass fiber powder.

[0084] Performance testing

[0085] 1. Thermal insulation performance test: Use electrostatic spraying to spray powder coating on an aluminum alloy test plate of 30cm×30cm×2mm in size. The back does not need to be sprayed and solidified to form a coating. Use an infrared lamp to irradiate for 1 hour at a distance of 0.5m from the coating surface. Test the average temperature on both sides of the test plate, and then calculate the thermal insulation temperature difference of the sample.

[0086] 2. Thermal reflectivity and thermal emissivity test: The test method is in accordance with GB / T 25261-2018 "Reflective Thermal Insulation Coatings for Buildings" standard.

[0087] 3. Adhesion test and aging performance test: Before spraying the powder coating, the surface of the test aluminum plate is pretreated according to GB / T 9286-2021. The surface-treated test aluminum plate is hung in the powder spray cabinet and sprayed with a spray gun for high-voltage electrostatic spraying. The test aluminum plate sprayed with the heat-insulating powder coating is placed in a blast drying oven for curing at a curing temperature of 200°C and a curing time of 10 minutes. After curing, the test aluminum plate is placed at room temperature for 24 hours, and the dry adhesion and accelerated weathering resistance of the coating are tested according to GB / T 5237.4-2008. The accelerated aging test is carried out in an artificial accelerated aging box QUV (Q-Lab instrument: accelerated aging test machine). According to the national standard GB / T 14522-2008, the sample is placed under ultraviolet light for 240 to 360 hours, and each cycle is 4 hours of condensation and 4 hours of radiation. Samples are taken at different intervals, and their color difference is tested and recorded.

[0088] Table 1

[0089]

[0090] According to the comparison between Example 1 and Comparative Example 1 and the data in Table 1, it can be seen that when the hollow glass microspheres and glass powder are directly added to the raw materials without modification, the compatibility of the hollow glass microspheres, glass powder and matrix resin is poor, and the interface bonding force between the microspheres and the resin cannot be improved, making it difficult for the glass microspheres and glass powder to form a cross-linked network with the resin, thereby affecting the thermal insulation performance of the coating. In addition, since the hollow glass microspheres and the matrix resin form a stable three-dimensional cross-linked network under the action of the composite coupling agent and have a suitable cross-linking density, the microspheres and the resin are no longer simply physically blended, but have excellent interface bonding, so that the coating has excellent weather resistance.

[0091] According to the comparison between Example 1 and Comparative Examples 2-3 and the data in Table 1, it can be seen that the modification effect of a single coupling agent on the hollow glass microspheres is not ideal, and the use of a silane coupling agent and an aluminate coupling agent to prepare a composite coupling agent, and the composite coupling agent to modify the hollow glass microspheres can improve the compatibility with the resin, and the silane coupling agent and the aluminate coupling agent both have a synergistic effect on the hollow glass microspheres, and the compatibility between the modified hollow glass microspheres and the matrix resin is optimal, which effectively improves the thermal insulation performance of the coating.

[0092] According to the comparison between Example 1 and Comparative Example 4 and the data in Table 1, it can be seen that when the modified hollow glass microspheres are not added, the heat reflection performance of the coating is poor. On the contrary, the hollow glass microspheres have the characteristics of being hollow and enclosing a certain amount of gas inside the sphere, so that the powder coating has excellent heat insulation performance, and can also reflect the visible light and near-infrared light in the sunlight multiple times, so that the coating with the modified hollow glass microspheres added has very good heat reflection performance, while the glass fiber powder does not have the heat insulation property.

[0093] According to the comparison between Example 1 and Comparative Example 5 and the data in Table 1, it can be seen that when the modified glass powder is not added, the thermal insulation performance and weather resistance of the coating are poor. On the contrary, after the modified glass powder is added to the raw material, the thermal insulation performance and weather resistance of the coating are significantly improved. Among them, the glass powder has a small particle size, good dispersibility and matting effect, and is filled in the gap between the resin and the interstitial glass microbeads to improve the aging resistance of the coating, while the glass fiber powder is mainly used as a reinforcing material.

[0094] According to the comparison between Example 1 and Examples 4-5 and the data in Table 1, it can be seen that the silane coupling agent containing a mercapto group has a better modification effect on hollow glass microspheres than the silane coupling agent containing an amino group or an epoxy group. Since the mercapto group is more active than the amino group and the epoxy group, it is easier to participate in the curing and cross-linking reaction with the resin matrix.

[0095] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A heat-reflective heat-insulating powder coating, characterized in that: The invention is prepared from the following raw materials by weight: 60-70 parts of polyester resin, 10-14 parts of hollow glass microspheres modified by composite coupling agent, 9-13 parts of glass powder modified by organic chromium compound, 3-5 parts of curing agent, 1-2 parts of glass fiber powder, 1.5-1.9 parts of leveling agent, and 1.2-1.6 parts of degassing agent; The composite coupling agent modified hollow glass microspheres are prepared from silane coupling agent, aluminate coupling agent and hollow glass microspheres, and the weight ratio of the silane coupling agent, aluminate coupling agent and hollow glass microspheres is (0.6-0.8): (0.2-0.4): 10; the organic chromium compound modified glass powder is prepared from methacryloyl chromium complex and glass powder, and the weight ratio of the methacryloyl chromium complex and glass powder is (0.3-0.5): 12; The silane coupling agent is at least one of (3-mercaptopropyl)methyldimethoxysilane and (3-mercaptopropyl)triethoxysilane; The particle size of the hollow glass microspheres is 20-40 μm, and the particle size of the glass powder is 4-8 μm; The polyester resin is a carboxyl-terminated polyester resin.

2. A heat-reflective heat-insulating powder coating according to claim 1, characterized in that: The aluminate coupling agent is at least one of di(distearic acid glyceryl) isopropyl aluminate and di(tristearic acid pentaerythritol) isopropyl aluminate.

3. The heat-reflective heat-insulating powder coating according to claim 1, characterized in that: The acid value of the carboxyl-terminated polyester resin is 40-60 mgKOH / g and the molecular weight is 4000-6000.

4. The heat-reflective heat-insulating powder coating according to claim 1, characterized in that: The curing agent is at least one of N,N,N',N'-tetrakis(β-hydroxyethyl)-1,4-cyclohexanediamide and N,N'-bis(β-hydroxyethyl)adipamide.

5. The heat-reflective heat-insulating powder coating according to claim 1, characterized in that: The leveling agent is at least one of polyacrylate and silicon-containing acrylate.

6. The heat-reflective heat-insulating powder coating according to claim 1, characterized in that: The degassing agent is at least one of ethylene bisstearamide and hydrogenated castor oil.

7. A method for preparing a heat-reflective heat-insulating powder coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: The raw materials are weighed according to the component ratio, the polyester resin is heated to 150-170°C, and then hollow glass microspheres modified by composite coupling agent, glass powder modified by organic chromium compound, curing agent, glass fiber powder, leveling agent and degassing agent are added and mixed at high speed for 20-30 minutes, the uniformly mixed materials are mixed and extruded, and after discharging, the sheets are pressed and cooled to room temperature, and then sieved after high-speed crushing to obtain heat-reflective heat-insulating powder coating.

8. The method for preparing a heat-reflective heat-insulating powder coating according to claim 7, characterized in that: The preparation method of the composite coupling agent modified hollow glass microspheres is as follows: ① Place the hollow glass microspheres in a NaOH solution, stir at 50-60°C for 3-4 hours, then wash with deionized water and alcohol alternately, filter under reduced pressure to remove excess water, and dry to obtain pretreated hollow glass microspheres; ② Mixing a silane coupling agent and an aluminate coupling agent to obtain a composite coupling agent, then adding the composite coupling agent to an ethanol solution, adjusting the pH to 5.0-7.0, hydrolyzing for 1-2 hours to obtain a hydrolyzed coupling agent solution, then adding the pretreated hollow glass microspheres to the hydrolyzed coupling agent solution, stirring at 50-60° C. for 3-4 hours, then washing with deionized water and alcohol alternately, and drying at 70-80° C. for 10-12 hours to obtain composite coupling agent modified hollow glass microspheres; The preparation method of the organic chromium compound modified glass powder is: ① Place the glass powder in a NaOH solution, stir at 50-60°C for 3-4 hours, then wash with deionized water and alcohol alternately, filter under reduced pressure to remove excess water, and dry to obtain pretreated glass powder; ② Add the pretreated glass powder to the methacryloyl chromium complex, stir at 50-60°C for 3-4 hours, then wash with deionized water and alcohol alternately, and dry at 70-80°C for 10-12 hours to obtain the organic chromium compound modified glass powder.

Citation Information

Patent Citations

  • Organic / inorganic composite microspheres with core-shell structures and preparation method and application thereof

    CN103626897A

  • High temperature resistant thermal barrier powder paint, preparation method and spraying method thereof

    CN107267029A

  • High-heat-insulation powder coating for aluminum profile and preparation method of high-heat-insulation powder coating

    CN115260880A

Cited By

  • Organosilicon high-temperature-resistant wave-transparent high-carbon-formation-rate heatproof coating

    CN121064722A